STRATEGI GURU PENDIDIKAN AGAMA ISLAM PADA SISWA DI SMP NEGERI 1 KESAMBEN JOMBANG - Kholisotum Maghfiroh; Ahsanatul Khulailiyah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2021)
Religious teachers have the responsibility to equip students' morals for improvement and devotion and faith in God Almighty. Therefore, the strategy of an Islamic religious education teacher is very necessary in instilling religious values ??in schools. The focus of this study aims to describe the strategy of the Islamic Religious Education Teachers in Cultivating Student Religious Values ??at SMPN 1 Kesamben Jombang. This type of research is a qualitative field research (field research). This study used a qualitative descriptive research design. Data collection techniques using interview techniques, observation, and documentation. Furthermore, the data were analyzed using a qualitative descriptive analysis method, namely in the form of writing data about the related data. The next step is to test the data wetness by extending the observation and triangulation. The results showed that the strategy of Islamic religious education teachers in cultivating students' religious values ??at SMPN 1 Kesamben Jombang was as follows: teachers can give examples and role models to their students, as well as provide good practice habits in the daily activities of students in learning activities and non-learning so that students remain in a straight line of religion despite the rapid flow of globalization, while the inhibiting and supporting factors of the PAI teacher strategy in planting religious values ??of students at SMPN 1 Kesamben, namely the lack of awareness in students about the importance of the program of value-planting. religious value.